Ethereal packet sniffing - Orebaugh, Angela (Jay Beale's open source security series, 2004)
This book provides system administrators with all of the information as well as software they need to run Ethereal Protocol Analyzer on their networks. There are currently no other books published on Ethereal, so this book will begin with chapters covering the installation and configuration of Ethereal. From there the book quickly moves into more advanced topics such as optimizing Ethereal's performance and analyzing data output by Ethereal. Ethereal is an extremely powerful and complex product, capable of analyzing over 350 different network protocols. As such, this book also provides readers